Social Inequalities in Non-ischemic Cardiomyopathies - Amiya, Eisuke (Frontiers in Cardiovascular Medicine, 2022)
Heart failure has various characteristics, such as etiology, clinical course, and clinical characteristics. Several studies reported the clinical findings of the characteristics of non-ischemic cardiomyopathy. There have also been issues with genetic, biochemical, or pathophysiological problems. Some studies have been conducted on non-ischemic cardiomyopathy and social factors, for instance, racial disparities in peripartum cardiomyopathy or the social setting of hypertrophic cardiomyopathy. However, there have been insufficient materials to consider the relationship between social factors and clinical course in non-ischemic cardiomyopathies. There were various methodologies in therapeutic interventions, including pharmacological, surgical, or rehabilitational and educational issues. However, interventions that could be closely associated with social inequality have not been sufficiently elucidated. I will summarize the effects of social equality, which could have a large impact on the development and progression of heart failure in non-ischemic cardiomyopathies.